A review on Active Constituents and Pharmacological Effects of Eriobotrya Japonica Lindl. (Loquat) - Ibrahim, Ruaa M. (Iraqi Journal of Pharmaceutical Sciences, 2021)
Eriobotrya japonica Lindl., named as loquat, is a subtropical fruit tree of the family Rosaceae which is well known medical plant originated in Japan and China. Loquat portions, like leaves, peels and fruits have been shown to possess various health usefulnesses. In Chinese classical medicine, it is vastly utilized in many illnesses, like gastroenteric disorders, diabetes mellitus, pulmonary inflammatory diseases and chronic bronchitis. Loquat plant contain many active constituents, such as flavonoids, carotenoids, vitamins, polyphenolic compounds, other that have many biological effects like anti-tumor, anti-diabetic, anti-inflammatory, anti-mutagenic, antioxidant, antiviral, antitussive, hepatoprotective and hypolipidemic activity.